Practical stability of nonlinear measure differential equations. (November 2018) - Cao, Yueju; Sun, Jitao
Abstract: The paper investigates the practical stability of nonlinear measure differential equations. We first introduce the concepts of the practical stability and the practically asymptotic stability for measure differential equations. Then inspired by the proof method of the variational stability results in generalized ordinary differential equations, we provide the practical stability criteria for the measure system by using Lyapunov functions. Finally, as a special case, the practical stability results for discrete systems are given to illustrate our results.